APLIKASI PELAYANAN PENGADUAN MAINTENANCE DIVISI TEKNIK BERBASIS ANDROID PADA PERGURUAN TINGGI RAHARJA - Aris Aris; Maryanih Maryanih; Syinthia Ricka Arrianti (UNIVERSITAS RAHARJA, 2019)
Development of Service System for engineering section in the form of Application Maintenance Request System, which is used to improve services only to management, namely staf. Customer satisfaction is a specific evaluation of the overall services provided by the engineering department. so that the satisfaction of service users in the engineering division can only be judged based on the experience that has been experienced during the service delivery process. Customer satisfaction, especially in the area of maintenance services, is a must so that the service is developed more broadly for lecturers and students. With the development of an application system maintenance requests from websites are changed to mobile, that is based on Android which can make it easier for users to make complaints with Android-based smartphones, so it is very helpful for the engineering section to accommodate all user complaints. This Android-based Maintenance Request application can report quickly any maintenance requests that come from the user to the engineering officer, so that it gets a more effective and efficient response in measuring the level of time during maintenance.